Batman '89 - Hamm, Sam (DC Comics, 2025)
"Continuing the adventures of the Dark Knight from Tim Burton's classic movie Batman, Batman '89 pulls on a number of threads left dangling by that film while continuing in the tradition of DC's very successful Batman '66 series. In1989 moviegoers were amazed at the new vision of the Dark Knight brought to the screen by filmmaker Tim Burton, starring Michael Keaton as Batman and Jack Nicholson as The Joker. Now, in the tradition of DC's very successful Batman '66 series, Batman '89 is set in a truly gothic Gotham City and features colorful villains including The Joker, Two-Face, and many more."